Gestão de cooperativa: um estudo relacional do modo de organização do trabalho e desempenho organizacional no ramo de transportes de pessoas - Barbosa, José Elber Marques (2010)
Studies of work organization and its relationship with the results of operations in private and public organizations are multiplying in all degrees of school, however when asked about the relationship between these parameters in the cooperative activity there is a gap proportional to the importance of the subject. We see, however, cooperatives are started in various countries, excluding, in part, its philosophical and political ideologies. In Brazil, the cooperatives have been operating in various economy areas providing economic and social development. In this scenario, where there should be mass application of individual efforts, transforming them into collective effort, there is sharing of interests and compromise less with its own organization. In the case of people s transportation cooperative, these are inserted in a different block, especially in the Northeast of Brazil, where activities related to tourism grow above the average for other productive activities, in the initial stages, is not observed in the cooperatives established in the the region. Thus, the study objective is to identify the relationship between work organization mode and organizational performance of people transportation cooperative in the state of Paraiba. For this purpose, we used for basic research, descriptive, documentary and field, with qualitative and quantitative approach from questionnaires given to subjects, selected by stratified proportional sampling, of a population of 260 members and was realization the semi-structured interviews to presidents of the cooperatives. Then quantitative analysis we used the SPSS 8.0 software. For qualitative assessments was worked to analyze the content of words. The results, we found that the first cooperative of Paraiba was shaped Boxes Rural Raiffeisen, the organizations constitutive aspects show comprised mostly of married men with a mean age of 45 years and high school degree. The average monthly earnings, per each partner, is two thousand real (BRA) and the weekly work load of these is the 65-84h. The results achieved by the partners comprove their dependence on the performance of the cooperative. The solvency analysis revealed that the cooperatives studied have the ability to pay its financial commitments. And the influential variables of organizational performance, it follows that they are aligned to the internal structural elements - responsibility, power, leadership, command and control.